Lead-free (Ba, Sr)TiO3 – BiFeO3 based multilayer ceramic capacitors with high energy density. Issue 4 (April 2020) - Wang, Ge; Lu, Zhilun; Li, Jinglei; Ji, Hongfen; Yang, Huijing; Li, Linhao; Sun, Shikuan; Feteira, Antonio; Yang, Haoguang; Zuo, Ruzhong; Wang, Dawei; Reaney, Ian M.
Abstract: High recoverable energy density (10 J cm −3 ) multilayers have been fabricated from lead-free 0.61BiFeO3 -0.33(Ba0.8 Sr0.2 )TiO3 -0.06La(Mg2/3 Nb1/3 )O3 ceramics. High breakdown strength > 730 kV cm -1 was achieved through the optimisation of multilayer processing to produce defect-free dielectric layers 7 μm thick. Excellent temperature, frequency, fatigue stability and fast charge-discharge speed were observed in the multilayer, critical for their potential use in power electronics.